Relationships between vaccination, age, and mortality in the COVID-19 intensive care patients - Demir, İsmail; Yılmaz, Rasim Selçuk; Köse, Betül; Özkarakaş, Hüseyin; Çalık, Şebnem (The European Research Journal, 2022)
Objectives: To investigate the effects of vaccination on age, mortality, and healthcare workers among patients followed in the COVID-19 Intensive Care Unit. Methods: We examined age, gender, occupation, demographic characteristics, comorbid diseases, hemogram, biochemistry parameters, coagulation tests, morbidity–mortality characteristics of 548 patients in Bozyaka Training and Research Hospital COVID-19 intensive care unit admitted between March and October 2021. In addition, the vaccination status of the patients and the type of vaccination were recorded via the Ministry of Health Vaccine Tracking System (VTS). Within the vaccine follow-up system, patients who received at least 2 doses of vaccine 4 weeks prior to study were considered vaccinated. Results: The data of 548 patients in the COVID-19 intensive care unit between March 2021 and October 2021 were analyzed. The mortality rate was 50.7% (n = 278). It was determined that 428 (78.1%) of the patients followed in the COVID-19 intensive care unit were not vaccinated. In terms of age distribution, the number of patients under the age of 65 was 357 (65.1%), while the number of patients aged 65 and over was 191 (34.9%). When mortality rates were compared based on vaccination status, the mortality rate in the unvaccinated group was found to be statistically significantly higher than in the vaccinated group (p < 0.05). Mortality rate in the vaccinated group was 12.5% whereas it was 61.4% in the unvaccinated group. Conclusions: Vaccination to protect against SARS-CoV-2 infection reduces intensive care unit admission and reduces mortality rates. Being unvaccinated increases hospitalization and mortality in intensive care units in addition to carrying risks for all age groups.